Spatial Distribution of the Pepper Blight (Phytophthora capsici) Suppressive Microbiome in the Rhizosphere - Li, Huixiu; Wang, Ning; Ding, Jia; Liu, Yingjie; Ding, Xiaoyan; Wei, Yuquan; Li, Ji; Ding, Guo-chun (Frontiers in Plant Science, 2022)
The properties of plant rhizosphere are dynamic and heterogeneous, serving as different habitat filters that are for or against certain microorganisms. Herein, we studied the spatial distribution of bacterial communities in the rhizosphere of pepper plants treated with a disease-suppressive or non-suppressive soil. The bacterial richness was significantly (p<0.05) higher in plants treated with the disease-suppressive soil than in those treated with the non-suppressive soil. Bacterial richness and evenness greatly differed between root parts, with decrease from the upper taproot to the upper fibrous root, the lower taproot and the lower fibrous root. As expected, the bacterial community in the rhizosphere differed between suppressive and non-suppressive soil. However, the spatial variation (36%) of the bacterial community in the rhizosphere was much greater than that explained by soils (10%). Taxa such as subgroups of Acidobacteria, Nitrosospira and Nitrospira were selectively enriched in the upper taproot. In vitro Bacillus antagonists against Phytophthora capsici were also preferentially colonized in the taproot, while the genera such as Clostridium, Rhizobium, Azotobacter, Hydrogenophaga, Magnetospirillum were enriched in the lower taproot or fibrous root. In conclusion, the spatial distribution of bacterial taxa and antagonists in the rhizosphere of pepper sheds light on our understanding of microbial ecology in the rhizosphere.